OPTIMALISASI PENCATATAN ADMINISTRASI PERGUDANGAN MELALUI KEGIATAN INPUT STOCK OPNAME DAN MONITORING LOADING TIME PADA DEPARTEMEN WAREHOUSE FINISH GOODS DI PT XYZ - Putri Avrillia; Nurul Azizah (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to find out how the process of recording warehouse administration at PT XYZ focuses on stock taking activities and monitoring loading time. Stock Opname is an important process to ensure a balance between the physical quantity of goods and the administrative system. Meanwhile, monitoring loading time is an activity to monitor the duration of the loading truck during the loading process. This research was conducted through direct observation, interviews and documentation with warehouse heads, warehouse admins and other warehouse employees. Through dividing space in warehouse storage, employee training, using technology in the process of timing trucks in and out can increase operational effectiveness and efficiency. By implementing good procedures, companies can reduce errors in recording, increase inventory accuracy, and speed up the goods delivery process, which ultimately supports better business continuity.